Low-fat cheeses technology - Mayta-Hancco, Jhony (2020)
Low-fat cheeses are characterized as having poor flavour, texture and functional properties due to the high moisture and protein content. Some strategies developed to improve these deficiencies include the use of adjunct cultures, use of fat replacers and processing techniques. The use of adjunct cultures (mainly Lactobacillus spp) can improve the functionality and flavour of low-fat cheeses. It is desirable to have cultures of low proteolytic activity, but of high peptidolytic activity (to avoid excessive acid formation and bitter flavours). The use of fat stabilizers, replacers and fat mimetics (protein and carbohydrate based) has also been used to improve the quality of low-fat cheeses. Processing techniques, such as membrane processes (ultrafiltration and microfiltration), supplementation of milk with whey proteins, direct addition of buttermilk, standardization of milk in terms of casein/fat ratio and homogenization have been used to improve the texture, performance and functional properties of low-fat cheeses.